The Influence of Self Actualization Needs, Self-Esteem Needs and Social Needs on Employee Work Performance at the Paguyaman Pantai District Health Center, Boalemo Regency, Gorontalo Province - Nur Rahmi; Sri Meike Jusup (Universitas Muhammadiyah Palu, 2024)
This research aims to determined the magnitude of the influence of Self-Actualization Needs (X1), Self-Esteem Needs (X2) and Social Needs (X3) on Employee Work Performance (Y) in 55 employees of the Paguyaman Pantai District Health Center. using the survey method in determining respondents and Analysis Path to analysis methods, the test results shown that the variables Self-Actualization Needs (X1), Self-Esteem Needs Needs (X2) and Social Needs (X3) simultaneously have a positive and significant effect on Employee Work Performance (Y) of 0.885 or 88.5%. Partially, the Self-actualization needs variable (X1) has a positive and significant effect on Employee Work Performance (Y) of 0.212 or 21.2%. The Self-Esteem Needs variable (X2) has a positive and significant effect of 0.361 or 36.1% on Employee Work Performance (Y) and the Social Needs variable (X3) has a positive and significant effect of 0.461 or 46.1% of Employee Work Performance (Y) at the Community Health Center Paguyaman Pantai District.